Extending Documentation‐Based Models towards an Efficient Integration into Commercial Process Simulators. Issue 7 (11th June 2014) - Merchan, Victor Alejandro; Tolksdorf, Gregor; Kraus, Robert; Wozny, Günter; Nilles, Michael; Wozny, Günter
Abstract In this contribution an extension of the principle of modeling in the documentation level towards the model integration in process modeling tools is presented. The definition of documentation‐based, problem‐specific interfaces allows a highly specific code generation of customized user models, including physical property calls and port definitions, while keeping the model development at a tool‐independent level. Two case studies concerning the rigorous model development and simulation of multiphase liquid systems show the potential of this approach.